2016
DOI: 10.1155/2016/5912146
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation Mitigates Alzheimer’s Disease by Reducing Inflammation: A Randomized Controlled Trial

Abstract: Background/Aims. Low serum folate levels can alter inflammatory reactions. Both phenomena have been linked to Alzheimer's disease (AD), but the effect of folic acid on AD itself is unclear. We quantified folate supplementation's effect on inflammation and cognitive function in patients with AD over the course of 6 months. Methods. Patients newly diagnosed with AD (age > 60 years; n = 121; mild to severe; international criteria) and being treated with donepezil were randomly assigned into two groups with (inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 46 publications
1
115
0
2
Order By: Relevance
“…Supplementing with folic acid, Chen et al . revealed a beneficial response in patients with Alzheimer's disease as measured against cognitive function tests.…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Supplementing with folic acid, Chen et al . revealed a beneficial response in patients with Alzheimer's disease as measured against cognitive function tests.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Supplementing with folic acid, Chen et al 17 Papakostas et al 7 investigated the use of L-methylfolate augmentation in SSRI-resistant patients with major depression. The patients on these trials were prescribed sertraline, escitalopram, fluoxetine, or paroxetine during the investigation.…”
Section: Biochemistry Of L-methylfolatementioning
confidence: 99%
“…For instance, folic acid supplementation mitigated Alzheimer's disease and improved cognitive function in Chinese elderly with MCI via lowering the levels of peripheral inflammatory cytokines. 11 Guest et al observed an inverse association between cerebro-spinal fluid (CSF) folate and CSF levels of IL-6 in a healthy human cohort. 12 Folic acid protects motor neurons against the increased homocysteine, inflammation and apoptosis in SOD1 G93A transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
“…The anti‐inflammatory effect of folic acid has been widely reported in various clinical conditions. For instance, folic acid supplementation mitigated Alzheimer's disease and improved cognitive function in Chinese elderly with MCI via lowering the levels of peripheral inflammatory cytokines . Guest et al observed an inverse association between cerebro‐spinal fluid (CSF) folate and CSF levels of IL‐6 in a healthy human cohort .…”
Section: Introductionmentioning
confidence: 99%
“…Donepezil hydrochloride is an acetylcholinesterase inhibitor (AChEI) which inhibits the action acetylcholinesterase (AChE) in neuronal synapses, rendering increased acetylcholine action for better cognition [7,8]. AD patients are also found to be deficient for Vitamin B 12 , which has a striking effect on cognitive dysfunction [9,10,11].…”
Section: Introductionmentioning
confidence: 99%